In vitro activity of dihydrofolate reductase inhibitors and other antibiotics against Gram-positive pathogens collected globally between 2004 and 2016. (March 2019) - Noviello, Stephanie; Hawser, Stephen; Sader, Helio; Huang, David B.
Highlights: In vitro activity of iclaprim and comparators against 7618 Gram-positive clinical isolates. Iclaprim MIC50/90 values were 0.06/0.12 μg/mL for Staphylococcus aureus, including MRSA. Iclaprim MIC50/90 values were 0.03, 0.5 and 0.06 μg/mL, for S. pyogenes, S. agalactiae and S. dysgalactiae . Iclaprim was more potent than trimethoprim, vancomycin, linezolid, and daptomycin. Iclaprim had potent, consistent activity in Gram-positive isolates collected from 2004-2016. Abstract: Objectives: The objective of this study was to determine the in vitro activity of iclaprim and comparator agents against 7618 Gram-positive clinical isolates collected in the periods 2004–2006, 2012–2014 and 2015–2016. Methods: Antimicrobial susceptibility testing was performed by the broth microdilution method and the minimum inhibitory concentrations (MICs) were interpreted according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Iclaprim MIC50 /MIC90 values were 0.06/0.12 μg/mL for Staphylococcus aureus, including methicillin-susceptible and methicillin-resistant strains, and 0.015/0.03, 0.12/0.5 and 0.03/0.06 μg/mL, respectively, for Streptococcus pyogenes, Streptococcus agalactiae and Streptococcus dysgalactiae over 8 years within the period from 2004 to 2016. Iclaprim was 8–32-fold more potent than trimethoprim. Against S. aureus, including methicillin-resistant strains, iclaprim was more active than standard-of-care intravenous antibiotics used to treat Gram-positive skin infections. Iclaprim was up to 16-fold more potent than vancomycin and linezolid and was 4–8-fold more potent than daptomycin. Conclusions: Iclaprim demonstrated potent and consistent activity among Gram-positive clinical isolates collected globally between 2004 and 2016.